The Dynamic of Functional Microbes Community Under Auri (Acacia auriculiformis Cunn. Ex Benth) Agroforestry System - Widyati, Enny; Siarudin, Mohamad; Indrajaya, Yonky (Jurnal Manajemen Hutan Tropika, 2022)
Microbes are important rhizosphere constituents for providing nutrients in the soil. This study analyzes the dynamic of soil functional microbes’ populations on land managed as an agroforestry (AF) system. The AF system consists of a 2-years old auri tree combined with several crops, i.e., wild grasses, peanuts (Arachis hypogaea), pigeon pea (Cajanus cajan), and maize (Zea mays). Soil samples were collected from each rhizosphere and then analyzed for their chemical properties such as N, P, K, pH, and C organic contents. The population of functional microbes was observed by isolation of the non-symbiotic N-fixer microbes (BNF), the cellulose-degrading microbes (CDM), and the phosphate solubilizing microbes (PSM) in their selective media. The total soil sugars were also tested for root exudates. The results showed that in an auri agroforestry system, the kind of crops determines the content of the soil organic material that is turned-offer into the soil. This affects the population structure and functional microbial abundance in the rhizosphere. Furthermore, microbial colonization in the rhizosphere affects plants in producing root exudates. Then, root exudates shape the structures of the microbial community, as well as an influence among inhabitants in defining mineralization of soil organic matter, nutrient availability, and trees performance.